Review of Factors Controlling Skid Resistance at Tire-Pavement Interface - Abhinav Kumar; Ankit Gupta (Advances in Civil Engineering)
Road safety is of prime importance for pavement engineers and maintenance authorities. Pavement resistance to skidding of the vehicle has long been recognized as one of the leading parameters governing road safety and driving comfort, especially in wet weather conditions. The knowledge of skid resistance offered by pavement surface is very valuable information for road safety enhancements. Skid resistance is defined as the force developed when a tire that is prevented from rotation slides along the pavement surface. Evaluation of skid resistance over time and estimation of factors influencing it are important for pavement maintenance and rehabilitation planning. This paper presents a state-of-the-art review of various research works carried out for assessing critical parameters like surface texture, tire tread, rain intensity, temperature, loading condition, tire inflation pressure, and pavement type which control skid resistance of asphalt pavement at tire-road interface significantly. First, a brief overview of skid resistance and its importance in asphalt pavement is provided. Then, critical parameters influencing skid resistance are identified and reviewed more elaborately. Furthermore, the key relationship between skid resistance and various controlling parameters is reviewed and presented for a better understanding of skid variation analysis. Finally, a general discussion on skid resistance governing factors, their relative importance in maintaining safety and pavement performance, the complexity involved in computation, and established relationships with skid resistance is briefly summarized.